Sistem Pengendali Keamanan Sepeda Motor Berbasis IoT (Internet of Things) Menggunakan Smartphone Android - Edo Irawan; Ari Muzakir (Journal of Information Technology Ampera, 2022)
Motorbike vehicles are the most widely used private transportation by people to travel to places near and even far. In addition to motorcycles having a price that is relatively affordable by the public, motorcycles are much easier to go through all the congested and narrow road terrains. The increasing number of motorcycles circulating around and also the weak security system of motorcycles are one of the causes often targeted by theft. In this study, we provided a solution to this security by building a motorcycle security control system that can be accessed and controlled remotely using a Smartphone. The system installed on this motorcycle uses a microcontroller (Arduino Mega2560), a global positioning system (GPS) module, a vibration sensor module, and a relay module. The GPS module helps to determine the coordinates of the position of the motorcycle. These coordinates are sent and displayed through the Android application on the smartphone of the motorcycle owner. Based on the results of several tests, the system used can communicate well between the motorcycle and the motorcycle owner through the internet network, as long as the devices in the vehicle are connected to the internet network.